ANALYSIS OF THE CRITICAL WORK "BIOGRAPHY LITERARIA" BY SAMUEL TAYLOR COLERIDGE - Farmanov Gayrat (PEDAGOGS, 2024)
Abstract; A critique of the qualities of Wordsworth's poetry concludes the volume. available. Chapter XIV is the origin of the popular critical concept of "suspension of disbelief by the will" in the reading of poetic works. When the God of Colerid created nature, He made nature reflect the official qualities of the Son, the second person in the Trinity